Defining features of decorating sanitary-hygienic products by the method of flexographic and digital printing - Havenko, Svitlana; Dovhanych, Valentyna; Kochubei, Viktoria (Eastern-European Journal of Enterprise Technologies, 2025)
The intensive use of tissue products encourages manufacturers to search for new technologies for their decoration and researchers to study the factors influencing the quality of finished products. Flexographic printing is used to decorate sanitary and hygienic products, which is effective for large print runs. Digital printing is recommended for producing tissue products with small print runs. Therefore, the object of this study was flexographic and digital ink-jet imprints. As a result of the research, it was found that in the range from 50 to 100 % of the printed control scale, the optical density of all CMYK colors on a flexographic imprint is twice as high as in digital printing. The optical density of digital imprints increases in proportion to the color saturation. The optimal amount of luminophore that provides the luminescence effect of printed images on flexographic imprints has been determined. In the process of printing, tissue paper is exposed to temperature conditions. Thermogravimetric studies of printing inks with luminophore additives and corresponding imprints were conducted. Initial thermo-oxidative processes in the ink composition begin to develop at temperatures above 187 °C. A slight loss of mass (1.1 %) of the composition is observed in the range of 187–236 °C, which is accompanied by a deviation of the DTA channel into the region of exothermic effects due to the thermal oxidation of the luminophore. The influence of tissue products’ structure and printing area on punching resistance has been shown. Using the Kendall concordance coefficient, the degree of consistency of experts’ opinions regarding the priority of factors influencing the quality of tissue products was determined